Thought and action: Event-related potentials and behaviour in a primed and speeded lexical decision task. - Conder, Blanche. (University of Ottawa (Canada), 1994)
To examine the relation between cognitive and response processes, event-related potentials (ERPs) were recorded from 10 subjects during semantically primed lexical decisions in an Accuracy condition (response deadline 700 msec) and a Speed condition (deadline 450 msec). Targets were the prime's antonym, an unrelated word, or a nonword. The Speed condition reduced response time (RT) and accuracy, but not the latency of ERP deflections. RT varied with the amplitude of negativity 250-450 msec only for semantically primed targets. RT was dissociated from the N400 deflection elicited by unrelated and nonword targets. Individual differences in task performance and ERPs suggested that the most accurate subjects favoured early motor inhibition and data-driven processing, whereas slightly faster but significantly less accurate subjects relied on resource-driven processing. Regardless of RT condition, individual differences in processing, and positive response priming, the probability of correctly rejecting a nonword began to rise monotonically after the N400 peak and approached.90 before the peak of the late positive complex. Continuous transmission of response selection information to motor processes before stimulus evaluation processes have been completed is consistent with a parallel distribution of word recognition and response production processes.
Keywords: Psychology, Experimental.